AB0584 Systemic Sclerosis Sine Scleroderma: An Infra-Diagnosed Disease?. (15th July 2016) - Martinez-Vidal, A.I.; Freire, M.; Soto-Peleteiro, A.; Sousa-Dominguez, A.; Villaverde-Alvarez, I.; Vázquez-Triñanes, C.; Lorenzo-Castro, R.; Argibay, A.; Rivera, A.
Abstract : Background: Systemic sclerosis (SSc) is a connective tissue disease of unknown origin, with heterogeneous clinic presentation and chronical and progressive evolution. There is a subtype of SSc without cutaneous presentation designated as systemic sclerosis sine scleroderma (ssSSc) that is difficult to diagnose with a delay on it producing worse prognosis. Objectives: The objective of this study was analyzing demographic features, clinical presentations, the treatment and evolution of ssSSc patients from our hospital. Methods: There were analyzed in a retrospective way the patients diagnosed of SSc in our center between 1990 and May 2015, selecting those with ssSSc. Results: Among the 106 patients diagnosed of SSc in this period, only 5 patients (4.7%) had ssSSc. All of them were women with an average of 51 years. 3 patients (60%) had additionally an autoimmune hypothyroidism, other a polyglandular autoimmune syndrome and the other one had no autoimmune disease. Only one patient (20%) was HTA, another was smoker and another one had dyslipidemia. None of the 5 patients had suffered exposure to toxic elements. Average time delay for diagnosis was 10 years. For 3 patients initial diagnosis was in one case primary Raynaud phenomenon, other case pulmonary arterial hypertension (PAH) essential and in another one polyglandular autoimmune syndrome. 2 of the ssSSc diagnosis were done in 2006 (coincident with the opening of our monographic office of autoimmune systemic diseases). The reason for consultation in 4 of the patients (80%) was Raynaud phenomenon (RP) that was present in all of the patients during the tracking. Only one patient (20%) had digital ulcers, 2 patients (40%) esophagitis and 1 tendinopathy. 1 patient (20%) had PAH confirmed by right coronary angiography. All patients had antinuclear antibodies (ANA) positive, 80% anticentromere. A patient presented positivity to Anti Ro and another one to anticardiolipin antibodies. Nailfold capillaroscopy was made to 4 patients (80%), being all of them pathologic (Cutolo's pattern 3 active and 1 early). Spirometry was made in 4 patients (80%) founding diffusion alteration in 3 of them. The transthoracic echocardiogram performed to all patients was pathologic in the 3 of them (60%) (1 patent ductus arteriosus, 1 PAH and 1 valvular heart disease). Regarding treatment, 3 patients (60%) were treated with calcium antagonists and 2 (40%) received bosentan, without presenting none of them any serious adverse effect. It is important to highlight that 2 patients (40%) developed limited scleroderma after 9 and 4 years of diagnosis respectively. The patient with PAH died during the tracking because of right heart failure. Conclusions: ssSSc diagnosis is difficult due to the absence of the main presentation, the cutaneous one. The most frequent beginning symptom is the RP, so including this symptom in the anamnesis and stablishing screening measures in patients with RP with detection of ANAs and periungual capillaroscopy is important for an early detection to allow diagnosis improvement. References: Sehriban Diab et al. Systemic Sclerosis Sine Scleroderma: A Multicenter Study of 1417 subjects. The Journal of Rheumatology (2014) 41:11. Sophie P et al. The many faces of scleroderma sine scleroderma: a literature review focusing on cardiopulmonary complications. Rheumatol Int (2009) 29:861–868. Disclosure of Interest: None declared